2021
DOI: 10.3390/ijerph18073693
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Costs Associated with Complications in Patients with Type 2 Diabetes among 1.85 Million Adults in Beijing, China

Abstract: We aimed to provide reliable regression estimates of expenditures associated with various complications in type 2 diabetics in China. In total, 1,859,039 type 2 diabetes patients with complications were obtained from the Beijing Medical Claim Data for Employees database from 2008 to 2016. We estimated costs for complications using a generalized estimating equation model adjusted for age, sex, and the incidence of various complications. The average total cost for diabetic patients with complications was 17.12 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The results of our study confirmed that hospitalization and complications play a decisive role in the diabetes-related direct medical costs of diabetic patients, which is consistent with previous studies (15, [23][24][25][26][27][28]. Hospitalization is essentially a reflection of the severity of a diabetic patient's condition and a manifestation of poor control and management of diabetes (29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study confirmed that hospitalization and complications play a decisive role in the diabetes-related direct medical costs of diabetic patients, which is consistent with previous studies (15, [23][24][25][26][27][28]. Hospitalization is essentially a reflection of the severity of a diabetic patient's condition and a manifestation of poor control and management of diabetes (29).…”
Section: Discussionsupporting
confidence: 92%
“…In terms of complications, our research shows that the number and types of complications in patients with diabetes have a direct impact on their diabetes-related direct medical costs. This result highlights evidence from other studies that the medical costs caused by complications contribute to a high economic burden for patients with diabetes (15, [23][24][25][26][27][28]. The results of this study showed that the proportion of both patients with at least one complication and patients with multiple complications increased significantly from 2014 to 2019.…”
Section: Discussionsupporting
confidence: 85%
“…Previous research performed elsewhere reported high costs for care of acute diabetes complications [ 21 , 22 ] and higher costs per episode of hospitalization for acute diabetes complications as compared to those without [ 23 ]. In an analysis performed by Javor et al [ 23 ], it was shown that diabetes ketoacidosis triples the costs of hospital care for patients with type 1 diabetes in the US (USD 13,096 per hospitalization episode for diabetes ketoacidosis versus USD 4907 per hospitalization episode without ketoacidosis).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the Beijing Medical Claim Data for Employees (BMCDE) database have been previously described elsewhere. 17,18 Briefly, anonymous medical claim data, such as demographic characteristics, clinical diagnosis, medication and reimbursement information, of all active or retired employees enrolled in basic medical insurance in Beijing (nearly 90% of Beijing’s permanent population) were registered into the database. Because the data we used were retrospective information encrypted for administrative purposes, our research was exempt from ethics committee review.…”
Section: Methodsmentioning
confidence: 99%